The Influence Of Capital, Location, And Length Of Trading Toward’s Traders Income In Traditional Market After Revitalization (Study Of Legi Market In Parakan Temanggung) - Firmania, Fahma -; Karnowahadi, Karnowahadi -; Inayah, Inayah - (Admisi dan Bisnis, 2020)
The purpose of this research was to find out the effect of capital, location, and length of trading on traders income in traditional market after revitalization. The population in this study are all trader in Legi market totaling 3200 peoples. The sample used in this research are 97 peoples. This research used multiple regression analysis which consisted of the coefficient of determination, F test, and T test. The data were collected using questionnairs of likert scale. The result of this research shows that the percentage of influence between independent variables and the dependent variable was 17,2%. The result of statistical F test has significant value < significant level (0,000<0,05). It means that capital, location, and length of trading have significantly affected towards treders income. Partially, the capial and length of trading significantly affected towards treders income but the location doesn’t has significantly affected toward traders income and the regression equation was equal to P = 1,821 + 0,213M + 0,065L + 0,274LU.